Case Report: “Smart Palliation” and “Clepsydra Shape”: A new approach in complex congenital heart disease - Bellanti, Ermanno; Calaciura, Rita E.; Andriani, Ines; Saitta, Michele; Agati, Salvatore (Frontiers in Pediatrics, 2023)
A limiting factor in using vascular conduits in the pediatric/newborn population is their inability to grow. Many complex congenital heart diseases require palliative surgery, but using rigid and nonexpandable conduits does not allow the structures to grow and anticipates the need for redo surgery. In newborns, a way to increase the palliation time according to the patient's growth is desirable. In recent years, expandable shunts (exGraft™ PECA) have been developed. According to recent material studies, a shunt could increase diameter after endovascular balloon dilatation. In this case report, we describe the first case of endovascular Blalock-Thomas-Taussig shunt (mBT) shunt expansion in a Tetralogy of Fallot / atrial-ventricular Septal Defect complete (TOFAVSDc) patient with trisomy 21 who went to palliative treatment for tracheomalacia (noncardiac lesion association), severe pulmonary arteries hypoplasia, and low weight. This case introduces the “Smart Palliation concept” in the clinical scenario of selected growing patients where the lifetime of the Blalock-Thomas-Taussig (BT) shunt, anatomic substrates, and complexity of clinical status may require an additional palliation time. The limitation of endovascular conduit expansion is the fragility of the anastomosis site. The anastomosis site is a lesser strength structure of the conduit, and dilatation could develop procedure complications. For this reason, in this paper, we introduced our project design: a new technique (Clepsydra Shape) that consists, before surgical implantation, of pre-expansion of the proximal and distal anastomotic parts of the shunt to obtain an increase of 30% in size of both anastomotic sides, preventing stress- and stretch-related lesion of future balloon dilatation.